THE SECOND WORLD WAR IN AMERICAN LITERATURE - Student of CSPU The English language theory; practice department Boyqobilova Durdona Scientific advisor: Kenjayeva Muxlisa Baxodir qizi (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
In this paper, Wallace L. Woodcock conducts a detailed examination of the key novels of World War II in American literary works. The study covers elements like themes, writing styles, perspectives, values, language use, and overall direction found in forty-four novels authored by twenty-nine different writers. The thesis is structured into six chapters focusing on Techniques and Styles, Subject Matter, Attitudes and Values, Language, Humor, and a Comprehensive Evaluation. The included novels encompass a broad spectrum of viewpoints on the events of the Second World War, authored by notable writers such as Ludwig Bemelmans, Vance Bourjaily, Kay Boyle, and others listed in the text. Keywords: Prominent authors, historical events, American literature, realism, global conflict, challenges and tragedies of war, literary expression, complexities of war.